Russian banking associations as subjects of institutional changes - I. N. Shapkin (Мир новой экономики, 2019)
Market economy, as evidenced by historical practice, inevitably leads to the unification of entrepreneurs in public organizations.  In modern Russia, the formation of such structures began in the late 1980s.at that time, regional, sectoral and national associations were established. The oldest business unions were branch banking organizations, which United in their ranks banks and structures related to the banking business of the country. Bank associations are lobbying associations designed to form, formulate and communicate to the authorities the wishes of the organized banking community. There are various relations between the current state bodies and associations, which, as a rule, are not widely publicized, but which largely determine the state of the modern Russian economy, the nature and direction of the economic policy and strategy of the state. In addition to significant lobbying efforts aimed at creating favorable conditions for banks, the unions solve the problem of unification and standardization of banks, replication of the most successful domestic and foreign practices. They have become the most important subject of institutional changes not only in the financial segment of the economy, but also in the economy as a whole.  The purpose of the article is to identify the directions, mechanisms of influence and influence of banking associations on the financial and banking environment. It is written on the basis of open sources — the materials of the two largest banking unions of the country, as well as analytical materials on lobbying and the activities of business associations of the past and present.